2021
DOI: 10.3389/fpls.2020.635139
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Meiotic Crossovers Along Wheat Chromosomes by Virus-Induced Gene Silencing

Abstract: Meiotic recombination is the main driver of genetic diversity in wheat breeding. The rate and location of crossover (CO) events are regulated by genetic and epigenetic factors. In wheat, most COs occur in subtelomeric regions but are rare in centromeric and pericentric areas. The aim of this work was to increase COs in both “hot” and “cold” chromosomal locations. We used Virus-Induced gene Silencing (VIGS) to downregulate the expression of recombination-suppressing genes XRCC2 and FANCM and of epigenetic maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…In the case of anti-CO genes, although it has been reported that they act independently (Séguéla-Arnaud et al, 2015 ), double mutants do not necessarily result in a further CO increase. Thus, fancm on its own induced an increase in recombination in Arabidopsis , rice, and pea, but not in the subsequent studies in Arabidopsis F 1 hybrids (Crismani et al, 2012 ; Mieulet et al, 2018 ) or wheat (Raz et al, 2021 ). Moreover, the combination of fancm and recql4 did not show a further increase over recql4 in Arabidopsis or pea (Mieulet et al, 2018 ).…”
Section: Discussionmentioning
confidence: 85%
“…In the case of anti-CO genes, although it has been reported that they act independently (Séguéla-Arnaud et al, 2015 ), double mutants do not necessarily result in a further CO increase. Thus, fancm on its own induced an increase in recombination in Arabidopsis , rice, and pea, but not in the subsequent studies in Arabidopsis F 1 hybrids (Crismani et al, 2012 ; Mieulet et al, 2018 ) or wheat (Raz et al, 2021 ). Moreover, the combination of fancm and recql4 did not show a further increase over recql4 in Arabidopsis or pea (Mieulet et al, 2018 ).…”
Section: Discussionmentioning
confidence: 85%
“…In particular, fancm recombination phenotype seems to be sensitive to the hybrid context as it can be detected in brassica, pea, and rice but not in Arabidopsis, tomato and wheat hybrid lines. It was postulated that a high degree of polymorphism in the hybrid lines could interfere with fancm -dependent CO formation ( Blary et al, 2018 ; Mieulet et al, 2018 ; De Maagd et al, 2020 ; Raz et al, 2020 ).…”
Section: Engineering Meiotic Recombinationmentioning
confidence: 99%
“…The fancm mutants produce a significant increase in HR in diploid plants (Crismani et al, 2012;Li et al, 2021). However, silencing FANCM in tetraploid plants has less or no effect on recombination (Blary et al, 2018;Raz et al, 2021). This indicates that due to the specificities of tetraploid meiosis, the importance of certain molecular factors and complexes may increase or decrease.…”
Section: Discussionmentioning
confidence: 99%